2013
DOI: 10.2106/jbjs.l.00758
|View full text |Cite
|
Sign up to set email alerts
|

Fixation, Survival, and Dislocation of Jumbo Acetabular Components in Revision Hip Arthroplasty

Abstract: Jumbo acetabular components with screw fixation were associated with low rates of infection and loosening after revision total hip arthroplasty and had high survival at fifteen years. Reoperation for wear and loosening increased in the second decade. Dislocation was the most common complication and was significantly associated with smaller femoral head sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
2
46
1
9
Order By: Relevance
“…Delp et al [2] showed that superolateral placement of the hip center (2 cm superior and 2 cm lateral) decreases the moment arms of the hip abductors by an average of 28%, thus reducing force-generating capacity. Lachiewicz and Soileau [9] reported a dislocation rate of 10% after jumbo cup revision THA, which was the most common complication observed in their series. Hip center elevation in jumbo cup revision THA, as we observed, may be one of several factors that contribute to soft tissue laxity and hip instability.…”
Section: Discussionmentioning
confidence: 88%
“…Delp et al [2] showed that superolateral placement of the hip center (2 cm superior and 2 cm lateral) decreases the moment arms of the hip abductors by an average of 28%, thus reducing force-generating capacity. Lachiewicz and Soileau [9] reported a dislocation rate of 10% after jumbo cup revision THA, which was the most common complication observed in their series. Hip center elevation in jumbo cup revision THA, as we observed, may be one of several factors that contribute to soft tissue laxity and hip instability.…”
Section: Discussionmentioning
confidence: 88%
“…Gustke et al14) reported 196 hips had revisional arthroplasty with jumbo cup and mean followed for 10 years, the survival rate was 96%. The other study report the survival rate of jumbo cup is from 80% to 96%5789).…”
Section: Discussionmentioning
confidence: 95%
“…Using of jumbo cup with porous coated in revisional arthroplasty make greater host bone contract and peripheral rim fixation456). The survival rate of jumbo cup is relatively high from 80% to 96%5789). Some authors suggested that for better fixation of jumbo cup, peripheral rim fixation of acetabulum is essential10).…”
Section: Introductionmentioning
confidence: 99%
“…Such cups have been reported to last as long as 15 years. 11,12 The use of jumbo cups and augments has replaced the use of bulk allografts at our institution.…”
Section: Discussionmentioning
confidence: 99%